2023
DOI: 10.1108/josm-11-2022-0348
|View full text |Cite
|
Sign up to set email alerts
|

The nature of actor engagement intensity: a classification scheme

Abstract: PurposeActor engagement (AE) literature shows inconsistent understandings of engagement intensity. However, a holistic picture of the nature of AE intensity is foundational to advance empirical AE models and measurement frameworks. This paper provides a nuanced understanding of what engagement intensity is and how it unfolds on different network levels.Design/methodology/approachThis conceptual study draws from a literature review and offers a comprehensive classification scheme of AE intensity. The literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 97 publications
(424 reference statements)
0
8
0
Order By: Relevance
“…Azer and Alexander (2020) measured how the relative intensity of negative engagement can be moderated by the behaviors of other actors, highlighting the networked effect of engagement intensity. Wang et al (2023) observed the effects of engagement intensity at the individual, dyadic, and wider network levels, connecting it with actors' resource investments, relational strength, and the degree of connectedness in the network. In relation to valence, research has explored the interplay between forms of valence (positive, negative, and disengagement) (Hollebeek and Chen, 2014;Naumann et al, 2017) in offering typologies and discussing the impacts of negative engagement behaviors Alexander, 2018, 2020).…”
Section: Understanding and Managing Engagement Journeysmentioning
confidence: 99%
See 4 more Smart Citations
“…Azer and Alexander (2020) measured how the relative intensity of negative engagement can be moderated by the behaviors of other actors, highlighting the networked effect of engagement intensity. Wang et al (2023) observed the effects of engagement intensity at the individual, dyadic, and wider network levels, connecting it with actors' resource investments, relational strength, and the degree of connectedness in the network. In relation to valence, research has explored the interplay between forms of valence (positive, negative, and disengagement) (Hollebeek and Chen, 2014;Naumann et al, 2017) in offering typologies and discussing the impacts of negative engagement behaviors Alexander, 2018, 2020).…”
Section: Understanding and Managing Engagement Journeysmentioning
confidence: 99%
“…When CEBs directed at a focal object are increased, reduced, or even withdrawn, the quantity and extent of interactions are altered, and the introduction of new customers, partner organizations, and stakeholders to the wider service ecosystem is affected (Alexander et al, 2018;Dessart et al, 2015). Understanding the range of engagement behaviors, alongside their valence and intensity, can aid organizations in their social listening, helping them to identify key individuals who occupy central positions within a network, to incentivize certain behaviors at certain key journey stages, and to encourage imitation (Azer et al, 2023;Wang et al, 2023).…”
Section: Understanding and Managing Engagement Journeysmentioning
confidence: 99%
See 3 more Smart Citations